Trading secrets : spies and intelligence in an age of terror - Huband, Mark (I.B. Tauris, 2013)
Drawing on previously unseen material, unpublished letters and exclusive interviews, this title explores how the role and purpose of 'intelligence' has evolved from its origins in nineteenth-century Ireland to today's fight against terrorism.